Effects of Ranolazine on Torsades de Pointes Tachycardias in a Healthy Isolated Rabbit Heart Model. Issue 4 (August 2014) - Sossalla, Samuel; Wallisch, Nora; Toischer, Karl; Sohns, Christian; Vollmann, Dirk; Seegers, Joachim; Lüthje, Lars; Maier, Lars S.; Zabel, Markus
Abstract Purpose Torsades de pointes (TdP) tachycardias are triggered, polymorphic ventricular arrhythmias arising from early afterdepolarizations (EADs) and increased dispersion of repolarization. Ranolazine is a new agent which reduces pathologically elevated late INa but also IKr. Aim of this study was to evaluate the effects of ranolazine in a validated isolated Langendorff‐perfused rabbit heart model. Methods TdP was reproducibly induced with d‐sotalol (10−4 mol/L) and low potassium (K) (1.0 mmol/L for 5 min, pacing at CL 1000 ms). In 10 hearts, ECG and 8 epi‐ and endocardial monophasic action potentials were recorded. Action potential duration (APD) was measured at 90% repolarization and dispersion defined as APD max–min. Results D‐sotalol prolonged APD90 and increased dispersion of APD90, simultaneously causing EADs and induction of TdP. The combination of d‐sotalol and two concentrations of ranolazine did not increase dispersion of ventricular APD90 as compared to vehicle. Ranolazine at 5 μmol/L did not cause additional induction of EADs and/or TdP but also did not significantly suppress arrhythmogenic triggers. The higher concentration of ranolazine (10 μmol/L) in combination with d‐sotalol caused further prolongation of APD90, at the same time reduction in APD90 dispersion. In parallel, the incidence of EADs was reduced and an antitorsadogenic effect was seen. Conclusions In the healthy isolated rabbit heart (where late INa is not elevated), ranolazine does not cause proarrhythmia but exerts antiarrhythmic effects in a dose‐dependent manner against d‐sotalol/low K‐induced TdP. This finding—despite additional APD prolongation—supports the safety of a combined use of both drugs and merits clinical investigation.